2015
DOI: 10.1039/c5nr02974k
|View full text |Cite
|
Sign up to set email alerts
|

Self-doped Ti3+–TiO2as a photocatalyst for the reduction of CO2into a hydrocarbon fuel under visible light irradiation

Abstract: Self-doped TiO2 shows visible light photocatalytic activity, while commercial TiO2 (P25) is only UV responsive. The incorporation of Ti(3+) into TiO2 structures narrows the band gap (2.90 eV), leading to significantly increased photocatalytic activity for the reduction of CO2 into a renewable hydrocarbon fuel (CH4) in the presence of water vapour under visible light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
42
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 34 publications
3
42
0
2
Order By: Relevance
“…For the first issue, various approaches have been performed to make anatase TiO 2 sensitive to visible light, 6 and most of them are concerned on incorporating dopants at the O and/or Ti sites to introduce mid-gap states into the TiO 2 band gap. 7 As a result, the white color of TiO 2 might change, giving a clear sign that visible light has been absorbed. 8 Nevertheless, impurity incorporation can result in thermal instability and increasing carrier recombination centers.…”
Section: Introductionmentioning
confidence: 99%
“…For the first issue, various approaches have been performed to make anatase TiO 2 sensitive to visible light, 6 and most of them are concerned on incorporating dopants at the O and/or Ti sites to introduce mid-gap states into the TiO 2 band gap. 7 As a result, the white color of TiO 2 might change, giving a clear sign that visible light has been absorbed. 8 Nevertheless, impurity incorporation can result in thermal instability and increasing carrier recombination centers.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that TiO 2ÀX crystallinity and morphology can have a dramatic impact on photocatalytic properties. For example, TiO 2ÀX in the form of anatase, 14,22,23 rutile, 13,17,[24][25][26] and brookite 27,28 were studied as photocatalytic materials for water splitting under visible light, which is the most widely studied application. The use of titanium oxide, especially anatase, has also been studied for hydrogen generation by methanol photoreforming.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19] The molecular structure and atomicc onnectivity of PTCs can be accurately determined by single-crystalX -ray diffraction, [8] andt his makesi tm uch easier to understand their electronic properties and mechanisms compared with their heterogeneous counterparts (e.g., solid TiO 2 ). [14,[19][20][21] Therefore, studies on PTCs offer insights into optimal reaction conditions, detailedm echanisms, and structure-property relationships at the atomiclevel. [22,23] The geometrical and electronics tructures of PTCs are highly tunable by simply varying the experimental conditions( e.g., stoichiometric ratio of reactants, solvents, reaction time/temperature, coordinating ligands).…”
Section: Introductionmentioning
confidence: 99%